HUBUNGAN POLA ASUH ORANG TUA TERHADAP MASALAH MENTAL EMOSIONAL REMAJA - Dienda Febriani; Veny Elita; Sri Utami (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The parenting type is a way for developing adolescent mental emotional health. The purpose of this research was to determine the relationship between parenting type and adolescent mental emotional problem in SMK Negeri 2 Pekanbaru with non experimental research design with cross sectional method. Samples of this research involving 94 respondent that selective based on inclusion criteria using proportionate stratified random sampling technique. This research used parental authority questionnaire for parenting type variable and self-reporting questionnaire for mental emotional problem variable. This reaseach use univariat analysis to know about distribution of frequency and bivariat analysis to know about the correlation between two variables by using chi-square test. The result of this research showed that from 26 respondent with permissive parenting, 7 respondent (26,9%) do not have mental emotional problem and 19 respondent (73,1%) have mental emotional problem, 41 respondent with authoritarian parenting, 13 respondent (31,7%) have no mental emotional problem and 28 respondent (68,3%) have mental emotional problem, 27 respondent with demokratis parenting 18 respondent (66,7%) have no mental emotional problem and 9 respondent (37,3%) have mental emotional problem. Chi-square result shows p value (0,004) < alpha (0,05), which means that there was a relationship between parenting type and mental emotional problem in adolescent in SMK Negeri 2 Pekanbaru. Based on this research, it is suggested to the parents to use democratic parenting type in caring and educating adolescent.   Keywords: Adolescents, mental emotional problem, parenting type.